Optimal selection of tree species for ecological protection forests on the riverbank side of the lower Yellow River flood control dikes - Xiaolei Zhang; Kexin Li; Zhiheng Xu; Chaoqun Li; Zhengxiong Bai; Chen Yang (Ecological Indicators)
In the context of global climate change and frequent extreme floods in river basins, river floods pose a global challenge for flood management. Ensuring that flood control dikes do not breach is a fundamental principle of flood defense. The ecological protection forests on the riverbank side of dikes, as an important biological flood control measure, play a crucial role in mitigating the direct impact of floods on the dikes. Selecting appropriate tree species for these forests is one of the key factors in enhancing flood defense capacity. This paper first analyzes the construction needs and planning status of the ecological protection forests on the riverbank side of the Lower Yellow River dikes. Using remote sensing imagery analysis, typical years are selected to study the variation in vegetation coverage along the wide river sections from Huayuankou to Gao Village in the Lower Yellow River. Based on vegetation coverage, the current distribution of the ecological protection forests is analyzed in different river sections. Then, a TOPSIS-AHP coupled model is constructed for tree species selection, considering three primary indicators: wave dissipation capacity, growth characteristics, and auxiliary functions, as well as eight secondary indicators: root development, branch flexibility, vegetation height, etc. Interval numbers and triangular fuzzy numbers are introduced to address the difficulties in quantifying certain indicators, while the Analytic Hierarchy Process (AHP) is used to determine indicator weights. The model is applied to the Lower Yellow River, selecting eight plant species for optimization. The results show that willows, Chinese pagoda trees, and white wax trees are suitable species for the ecological protection forests on the riverbank side of the Lower Yellow River dikes, with willows being the optimal species, achieving a suitability score of 0.727.